31ST AVIATION FACTORY OF TBILISI AND ITS OPERATION WORLD WAR II (1939-1945) - Vili, Teimuraz Akhalmosulish (PT. Antis International Publisher, 2024)
the second world war has a special place in the history of humanity and it is an object of more attention. The war fundamentally changed the political landscape of the second half of the twentieth century and led the life of the peoples of the planet to a completely different economic order. In the epicenter of the development of the will of public care, Georgia, also found himself, what an invaluable contribution he made to the destruction of fascism. In this paper, we will discuss Georgia's contribution to the defeat of fascist Germany, using a brief example of Tbilisi's 31st aviation factory. From the very first day of the start of the war between Germany and the Soviet Union, the creation of the war budget of the public economy was subordinated to the heads of the country. The priority of the main state committee is the grand evacuation of production forces from the districts. It was in this region that he became a Georgian during the war. First, the beginning was taking place in Tbilisi. In 1941, the bell factory was rebuilt on the basis of this enterprise. G. Was evacuated. 31st aviation factory named after dimitrov. Tbilisi's 31st aviation age angry mainly launched LAGG-3 type bombers, yak-3 fighter jets, all the second world were one by one the best jet fighters jet fighters jet fighters. The factory completed the task of the state budget during the second world war. Among them, the factory produced dozens of thousand-high machine gun barrels, etc. Based on the general above, the purposeful ownership of the ring of initial defensive and military action led to the repulsion of the fascist aggression of Germany, destruction, destruction.